Development of multiparticulate systems based on natural polymers for morin controlled release - Sales, Luciana Solera [UNESP]; Gimenes, Milena da Silva [UNESP]; Meneguin, Andréia Bagliotti [UNESP]; Barud, Hernane da Silva; Achcar, Jorge Alberto; Brighenti, Fernanda Lourenção [UNESP] (Elsevier, 2023)
This study aimed to develop a multiparticulate system based on sodium alginate/gellan gum polymers for morin controlled release using standardized spray-dryer parameters. A 24 experimental factorial design was used to standardize spray-dryer parameters. After standardization, three systems with three different proportions of the natural polymers (50:50, 25:75, 75:25; sodium alginate: gellan gum) with and without morin (control) were developed. The systems were characterized according to its morphology and physicochemical properties. Next, the systems were evaluated regarding antibiofilm and antimicrobial activity against Streptococcus mutans. The factorial design indicated the use of the following parameters: i) air flow rate: 1.0 m3 /min; ii) outlet temperature: 120 °C; iii) natural polymers combination in different proportions; iiii) polymer concentration: 2 %. Scanning electron microscopy showed microparticles with spherical shape and rough surface. The samples released 99.86 % ± 9.36; 85.45 % ± 8.31; 86.87 % ± 3.83 of morin after 480 min. The systems containing morin significantly reduced S. mutans biofilm biomass, microbial viability and acidogenicity when compared to their respective controls. In conclusion, the spray-dryer parameters were standardized to the highest possible yield values and proved to be efficient for morin encapsulation and controlled release. Furthermore, these systems controlled important virulence factors of S. mutans biofilms.
Keywords: Biofilm; Gellan gum; Morin hydrate; Sodium alginate